Correlação entre os parâmetros do cortisol salivar e o fenótipo de fragilidade em idosos institucionalizados - Holanda, Cristina Marques de Almeida (2011)
Introduction: The Frailty Syndrome is characterized by the decrease of energy reserve and the reduced resistance to stressors. Studies indicate that the neuroendocrine markers can be related to the appearance of this syndrome. The main endocrine answer to stress is the increase of cortisol levels. Objective: To analyze the correlation between the frailty syndrome the salivary cortisol in elderly residing in nursing homes. Method: A traversal study was accomplished, in João Pessoa city, PB, with a sample composed by 69 institutionalized elderly. The collected data refer to the frailty phenotype (weight loss, exhaustion, slowness, weakness, and lower level of physical activity) and to salivary cortisol parameters (first measure - 6-7h; second measure - 11-12h; third measure - 16-17h). In the statistical analysis the Pearson s correlation test was used, Chi square Test and Anova and Simple Linear Regression analyses. Results: The sample was composed by 37.7% of men and 62.3% of women, with age average of 77.52 (±7.82). There was a percentile of 45.8% frail elderly. The frail elderly obtained higher cortisol values in the third measure (p=0.04) and the frailty load was significantly associated to the first measure (r=0.25, p=0.04). The simple linear regression analysis presented a determination rate (R2=0.05) between frailty load and first cortisol measure. Conclusion: The largest cortisol values in the morning and before sleeping among the frail elderly supply indications that can have a relationship of cortisol increase levels and the frailty presence in elderly from nursing homes.